Deixis Analysis in The Legend of Tangkuban Perahu Story - Gustia, Dewi Susi; Suryani, Lilis (PROJECT (Professional Journal of English Education), 2026)
This research would like to implement deixis. Deixis is the study of deictic or indexical statements in language dialogues, prologues, and monologues like you, now, today. This research aims to identify the types of deixis used in the legend of Tangkuban Perahu Story and realize the dominant types of deixis contained in the story of Tangkuban Perahu.  The writer focuses on three types of deixis: Personal Deixis, Spatial Deixis, and Temporal Deixis based on Cruse’s theory. This research used qualitative research. The steps to analyze data are finding the story from the internet, reading the story, determining the data based on the three kinds of deixis above, then calculating the appearance of each type of deixis used in the short story of the Tangkuban Perahu, and describing and explaining. The result of this research finding reveals kinds of deixis in the legend of Tangkuban Perahu story: personal deixis, spatial deixis, and temporal deixis. Based on the discussion, the most frequent came was personal deixis, with 96 or 91% deictic words, the second is Temporal deixis with eight or 7% deictic words, and Spatial deixis with two or 2 % deictic words.